Structural and ionic conductivity studies on proton conducting solid biopolymer electrolyte based on 2hydroxyethyl cellulose incorporated DTAB - N.H. Ahmad; N.Y. Bakar; M. I. N. Isa (American Institute of Physics (AIP) Publishing, 2024)
Indexed by SCOPUS